Emulsion liquid membrane extraction of silver from photographic waste using cyanex 302 as a mobile carrier - Othman, Norasikin; Chan, Kit Hie; Goto, Masahiro; Mat, Hanapi (2005)

(untitled)
The recovery of precious metals such as silver from photographic wastes is absolute necessity in order to save raw materials and to protect environment from hazardous compounds especially heavy metals. Several technologies have been used such as precipitation, electrolysis, and ion exchange processes offering some advantages as well as drawbacks over others. Recently, emulsion liquid membrane extraction has been recognized to be potential process for industrial wastes treatment and recovery of heavy metals. This process has enough ability to separate selectively and concentrating rapidly of the metals through its very thin layer liquid membrane having large interfacial area. An attempt was made to recover silver from liquid photographic wastes using with Cyanex 302 as a mobile carrier. The important variables affecting the emulsion liquid membrane (ELM) extraction process including extraction time, surfactant concentration, carrier concentration, stripping agent solution, level of agitation and phase treatment ratio between emulsion and feed phase were investigated. The results showed that the Cyanex 302 is selective towards silver more than 80% compared to other metals existed in the photographic waste. The highest silver extraction was obtained by using 0.05 M Cyanex 302, 3 % (w/v) Span 80, 250 rpm stirring-speed, 1.0 M thiourea in 1.0 M H2SO4 as stipping agent, 1:5 of treat ratio, and kerosene as a diluent.